PENGARUH M-BANKING DAN TINGKAT PENDAPATAN TERHADAP PENGELUARAN KONSUMSI MASYARAKAT DI KOTA PEKANBARU - , Yelly Zamaya, Maissy Sandhea Azura , Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the influence of the amount of money in m-banking transactions on public consumption expenditure in Pekanbaru City. Knowing the magnitude of the influence of income on public consumption spending in Pekanbaru City. The method used in this study is the people of Pekanbaru city who use mobile banking with an unknow population size. The sampling technique is purposive sampling. The number of samples in this study were 100 respondents. Data collection techniques using a questionnaire. The results of this study indicate that the total value of m-banking transactions has no effect on public consumption spending in Pekanbaru City. Income has a positive effect on public consumption spending in Pekanbaru City. M-banking and income levels effect public consumption spending in Pekanbaru City. Keywords: M-banking Transaction, Income, Expenditures